La ceramica d'uso comune a Gortina tra passato e futuro. Acquisizioni e nuove prospettive (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
Aim of the paper is twofold: first of all to draw a picture on the status quaestionis regarding the study of the plain ware at Gortyn, particularly for Roman and Late Roman periods, and secondly to outline some new research perspectives on this subject. The data collected thanks to the publications of the material brought to light in the recent excavations carried out in Gortyn allowed us to gain a clear image of the pottery production during these phases, for so long neglegted in the archaeological literature. But it’s surely with the study of the huge amount of pottery discovered in the archaeological investigations now carried out in different areas of the Roman settlement that we can improve (together with archaeometrical analyses, up to now not existing) the knowledge of the Gortynian plain ware in the different phases of its long history.
Keywords: Plain ware; Gortyn; Pretorium; basins; archaeometrical analyses